2019
DOI: 10.2196/12942
|View full text |Cite
|
Sign up to set email alerts
|

Public Opinions on Using Social Media Content to Identify Users With Depression and Target Mental Health Care Advertising: Mixed Methods Survey

Abstract: Background Depression is a common disorder that still remains underdiagnosed and undertreated in the UK National Health Service. Charities and voluntary organizations offer mental health services, but they are still struggling to promote these services to the individuals who need them. By analyzing social media (SM) content using machine learning techniques, it may be possible to identify which SM users are currently experiencing low mood, thus enabling the targeted advertising of mental health ser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 26 publications
(29 reference statements)
0
33
0
1
Order By: Relevance
“…It is clear that many actions taken by social media services are considered an invasion of user privacy, specifically regarding information about their mental health, with most of those actions falling under the category of intrusion . For example, a previous study mentioned that some social media users feel that it is intrusive their mental health status is profiled on social media forums (Ford et al, 2019). It may be difficult to find a balance between protecting every user's privacy on social media and using social media data for physicians to help individuals for their mental illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that many actions taken by social media services are considered an invasion of user privacy, specifically regarding information about their mental health, with most of those actions falling under the category of intrusion . For example, a previous study mentioned that some social media users feel that it is intrusive their mental health status is profiled on social media forums (Ford et al, 2019). It may be difficult to find a balance between protecting every user's privacy on social media and using social media data for physicians to help individuals for their mental illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of both missing information and misinformation generated by both individuals and automated bots emphasizes the need to design systems that use clear communication of potential risks to mitigate adverse consequences [38,39]. The use of social media for targeted advertising, particularly for sensitive topics such as mental health services, presents additional questions as to which applications of these data are considered to be acceptable [40]. A final concern relates to patient understanding of privacy risks as communicated by complex, evolving, and opaque terms and conditions on social media platforms [36,39].…”
Section: Social Media and Online Communitiesmentioning
confidence: 99%
“…The use of social media data for research has also had its own ethical challenges concerning privacy and informed consent 15,16 , as well as difficulty defining what mediums are included in the definition of social media at all 17 . A systematic review by Golder et al 18 in 2017 found that social media users and researchers tended to be conflicted about whether informed consent was necessary for data collected from public social media sites and, similarly to data linkage issues, this debate tended to rest on the nature of the content, which source the data came from and how the data would be used 14,[19][20][21] . Subsequent ethical guidelines developed for the field have placed special consideration on the reporting of social media research to ensure user's privacy 22,23 , and reflects participant's views that increased sensitivity and personal identifiability of the subject matter should increase the level of anonymity with which it is reported 15,19,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Within the UK the failure of the care.data program is cited as a reminder that even where data science initiatives are legal and technically feasible they can still fail if they lack the ‘social licence’ needed for public and key stakeholder support 10 . Existing research in the field of record linkage, outside of social media linkage, has found that there is a general acceptance of this work from the public 11 13 , even when conducted without consent if data is appropriately anonymised 13 , but that these decisions are ultimately complex and conditional on the situation 9 , 11 14 . Therefore, it is essential that any novel data linkage activity, or a novel use of existing data, is informed by exploring participant views towards its acceptability, as well as researchers exploring the participants understanding of the data and how it will be used.…”
Section: Introductionmentioning
confidence: 99%